Analysing costs of a facility-based lay health worker intervention focused on improving health outcomes for HIV positive women and children - Zeelie, Jean-Pierre (Department of Public Health and Family Medicine, 2014)
South Africa is facing a health care worker shortage which is contributing to poor health outcomes, especially in mother-to-child transmission of HIV. In order for Prevention of Mother to Child Transmission (PMTCT) programmes to achieve success, coverage needs to be dramatically increased. This paper aims to provide specifics on the costs of integrating a Lay Health Worker (LHW) into a clinic to improve patient uptake and retention of PMTCT services, in what was previously the Motheo district, Free State.